2021
DOI: 10.1182/blood.2021010913
|View full text |Cite|
|
Sign up to set email alerts
|

Somatic uniparental disomy mitigates the most damaging EFL1 allele combination in Shwachman-Diamond syndrome

Abstract: Shwachman-Diamond syndrome (SDS; OMIM: #260400) is caused by variants in SBDS (Shwachman-Bodian-Diamond syndrome gene), which encodes a protein that plays an important role in ribosome assembly. Recent reports suggest that recessive variants in EFL1 are also responsible for SDS. However, the precise genetic mechanism that leads to EFL1-induced SDS remains incompletely understood. Here we present three unrelated Korean SDS patients that carry biallelic pathogenic variants in EFL1 with biased allele frequencies,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…These alterations are associated with milder hematological phenotypes and a lower risk of developing MDS and AML ( Pressato et al, 2012 ; Valli et al, 2019 ; Valli et al, 2013 ), suggesting that hematological phenotypes are primarily caused by the continued presence of Tif6 on ribosomes, which blocks subunit joining. In addition, there is an SDS-like syndrome caused by mutations in EFL1 ( Stepensky et al, 2017 ; Tan et al, 2018 ; Lee et al, 2021 ; Tan et al, 2019 ), which may similarly prevent the timely release of eIF6 from the nascent ribosome.…”
Section: Ribosome Assembly At a Glancementioning
confidence: 99%
“…These alterations are associated with milder hematological phenotypes and a lower risk of developing MDS and AML ( Pressato et al, 2012 ; Valli et al, 2019 ; Valli et al, 2013 ), suggesting that hematological phenotypes are primarily caused by the continued presence of Tif6 on ribosomes, which blocks subunit joining. In addition, there is an SDS-like syndrome caused by mutations in EFL1 ( Stepensky et al, 2017 ; Tan et al, 2018 ; Lee et al, 2021 ; Tan et al, 2019 ), which may similarly prevent the timely release of eIF6 from the nascent ribosome.…”
Section: Ribosome Assembly At a Glancementioning
confidence: 99%
“…Less common mutations have also been reported throughout the gene including nonsense mutations, missense mutations, small deletions, indel conversions and splice-site mutations [ 10 , 11 , 12 , 13 , 14 ]. The rest of the patients (less than 10%) present clinical indications of SDS without having any pathogenic variants in SBDS but in other genes coding the proteins DNAJC21 [ 15 , 16 ], SRP54 [ 17 ] and EFL1 [ 18 , 19 , 20 , 21 ]. Importantly, the observed SBDS mutations result in a protein function drop that is responsible, when the SBDS levels are below a certain threshold, for a phenotype corresponding to the clinical manifestation of SDS.…”
Section: Introductionmentioning
confidence: 99%
“…The approach of whole-exome sequencing (WES) has disclosed genetic heterogeneity for SDS. Indeed, biallelic mutations in DNAJ homolog subfamily C member 21 (DNAJC21) (Tummala et al, 2016;Dhanraj et al, 2017), in GTPase Elongation Factor-like (EFL1) (Stepensky et al, 2017;Tan et al, 2018;Tan et al, 2019;Lee et al, 2021), or heterozygous mutations in the 54-kDa signal recognition particle (SRP54) (Carapito et al, 2017) have been reported in association with SDS or SDS-like phenotype in some patients.…”
Section: Introductionmentioning
confidence: 99%